The Determinant Factors of Inbound Tourists to Bali - Hariyadi (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2018)
This research intends to determine whether Bali Tourism has economic spillover effects on sub national area. The authors investigate those externalities through inbound and domestic tourism flows model by Yang and Wong (2012). In addition, another issue related to production factors migration (Capello, 2016) also covered in this paper. The result shows that air transportation plays a very important role in the inflow of tourism. Consequently, central and regional governments need to strengthen cooperation with the private sector in order to build and improve accessibility and domestic connectivity. Dealing with migration motive, it needs to increase local businesses participating in the national tourism industry.